Pengaruh Literasi Keuangan, Inklusi Keuangan dan Gender Terhadap Perilaku Pengelolaan Keuangan Pelaku UMKM di Kota Medan - Hutauruk, Rapat Piter Sony; Zalukhu, Rika Surianto; Collyn, Daniel; Jayanti, Suci Etri; Sinaga, Murbanto; Damanik, Sri Winda Hardiyanti (Accounting Progress, 2024)
The financial literacy and financial inclusion index of the Indonesian population has increased; however, most MSME actors still practice substandard financial management. In fact, financial management is vital for the development of MSMEs. Therefore, this study aims to analyze the influence of financial literacy, financial inclusion, and gender on the financial management behavior of MSME actors, both partially and simultaneously. This study examines three independent variables: financial literacy, financial inclusion, and gender, and one dependent variable: financial management behavior. The research was conducted on MSME actors in Medan City. The research sample consisted of 100 people, selected using a simple random sampling technique. This study used primary data. The research data were obtained through questionnaires distributed to respondents. The data obtained were then analyzed using multiple linear regression analysis methods. The analysis results show that financial literacy, financial inclusion, and gender have a positive and significant effect on the financial management behavior of MSME actors, both partially and simultaneously. The implication of this study is the need to develop inclusive and comprehensive financial education programs, increase access to financial services, and reduce the gender gap in financial access and literacy to improve the quality of financial management of MSMEs.